PENINGKATAN PEMAHAMAN SISWA PADA MATERI KOLOID MENGGUNAKAN PEMBELAJARAN MODEL SIKLUS BELAJAR 5E KELAS XI SMAN 2 PONTIANAK - Sartika, Rody Putra (Universitas Tanjungpura, 2016)
The purposes of this study are 1) to determine difference of conceptual understanding of SMA 2 Pontianak students before and after being taught through 5E learning cycle model on colloid subject matter, and 2) to describe conceptual understanding of SMAN 2 Pontianak Students before and after being taught through 5E learning cycle model on colloid material. This study was conducted in form of pre experimental design. Independent variables were learning before and after being taught through 5E learning cycle model. Dependent variable was students conceptual understanding. To collect data, assessment technique was applied and achievement test was used to get data. Data were analyzed by means of inferential and descriptive statistic. Result of statistic showed P-value = 0,000 < Î± = 0.05 which means that there was a difference of students conceptual understanding before and after being taught through 5E learning cycle model on colloid subject matter. Improvement of students conceptual understanding was 0,31 which means on average level. Key words: conceptual understanding, 5E learning cycle model.